The Important Role of Copyright in Preventing Theft and Promoting Innovation and Enterprise - Rosmayati, Siti (International Journal of Science Education and Technology Management, 2023)
Copyright is a legal instrument that plays a central role in encouraging innovation and protecting creators and creative entrepreneurs. This research uses a qualitative research approach to documentation studies. Through the exclusive rights it provides, copyright creates a basis of legal security for creators, giving them the freedom to innovate and develop works without fear of being stolen or imitated. Creators who feel their work is protected by copyright tend to be more motivated to create, creating an environment that supports the growth of creativity. Apart from that, copyright also plays an important role in promoting creative efforts. Creative entrepreneurs who know that their work is protected by copyright feel more secure in developing their business. Assurance that work is not easily stolen by competitors provides additional incentives to invest resources in product or service development, improving quality, and planning for long-term growth. The existence of copyright makes a positive contribution to the business and creative ecosystem, enabling creators and creative entrepreneurs to explore the full potential of their creativity. Therefore, copyright is not only a shield against theft of ideas, but also a vital driver in creating an environment that supports cultural, economic and innovation development in this global era.